Perspektif Generasi Muda Suku Karo Terhadap Kain Tradisional Suku Karo: Sebuah Analisis - Wesnina, _ (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
This study aims to find out how the knowledge or perspective of the younger generation of Karo tribe towards Karo tribe traditional cloth. Knowledge on the fabric (cloth) is includes the understanding on Karo traditional cloth, the name and meaning of Karo uis motifs, Karo traditional fabric and its characteristics, and the use of Karo traditional cloth in various cultural activities of Karo tribe. By using a descriptive qualitative method through a survey to the Karo younger generation whose both parents are from Karo tribes, this study found that generally the knowledge of young Karo tribe about traditional cloth. It can be concluded that the Karo young generation still have good and positive attention and the spirit in preserving the cultural and heritage of indigenous Karo tribe.